REFERENCES ON THE SPIRIT OF INTERPRENEURSHIP IN FORMING AN INDEPENDENT ATTITUDE OF STUDENTS AT UNIVERSITY - Junaedi, Deddy; Rahmawati, Dila; Alfiah, Dewi; Syafira, Karin; Qudsi, Qudsi; BZ, Zakiyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Instilling an entrepreneurial spirit in students is not an easy thing, as an active student you must be able to divide your time, so that the student's responsibilities can be completed perfectly, starting a business for students who have a creative and innovative spirit within themselves by channeling it through a business that can produce, so that students can have income to meet their needs. Being an independent student who owns a business can make a person more responsible, strategic, innovative and productive. Where students will become familiar with the responsibilities that must be carried out in order to become an experience that can motivate the future. As students living in an era of disruption, you should understand better what an entrepreneur is, where within this scope there is active interaction between producers and consumers. Being an independent student can of course influence many things in life, if students have the courage to start opening an online or offline business, then besides cultivating and having an entrepreneurial spirit, students can also have income that can be used for semester payments and daily needs, so that students can lighten the responsibilities of both parents towards him. Any business that students start requires a process for its achievement. With several references and the best strategies used, this can facilitate the achievement of the student's efforts. Because what students need in a business is not only enthusiasm but also a perfect marketing strategy, aimed at development so that it can be known to many people. Becoming an independent student is not only for experience and income, but can also make you a smart student, a student who can motivate others and the younger generation, where independent students can be used as a reference for those who want to start a business.